Diagnostic and therapeutic aspects of female sexual dysfunctions - Abdo, Carmita Helena Najjar (2006)
This article discusses the development of the concepts of normal and pathological in sexuality from the perspective of the population studies by Kinsey, as well as the development of the concept of sexual response cycle, from Masters and Johnson to Basson. The article deals with the classification of sexual dysfunctions, based on the sexual response cycle. Aspects of the diagnosis of female sexual dysfunctions reveal the importance of a detailed clinical observation, emphasizing that the diagnosis should take into account the length of the evolution period, the circumstances of the partner, and features of sexual stimulation (regarding focus, duration and intensity). Moreover, the distinction between primary or secondary and generalized or occasional dysfunction, as well as the age of the female patient and her sexual experience are parameters for a diagnosis. Therapeutic aspects indicate the importance of a multidisciplinary team, capable of offering psychotherapeutic and medicine-oriented treatment (antidepressants, anxiolytics and hormones, among others), as well as psycho-educational support. The authors stress the importance of a case by case evaluation in order to make a therapeutic decision. Although female sexual dysfunctions are already well known, the available therapeutic resources are limited. New research shall contribute to change this reality, so that the treatment of female sexual dysfunctions keeps up with the advances in the treatment of male sexual dysfunctions.